The Influence of Mobile Service and Economic Pricing on Consumer Preference in Bicycle Coffee Businesses - Mumud Saepul Muis Muis; Tita Miawati; Junengsih Junengsih (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
Development of mobile service-based coffee businesses has become an increasingly prominent phenomenon in urban microenterprise sectors, particularly those relying on flexible service locations and affordable pricing. In the Dago area of Bandung City, bicycle coffee businesses represent a form of physical mobile service that adapts to consumer mobility patterns. However, consumer preference toward this business model is influenced by service and pricing factors. This study aims to analyze the effects of Mobile Service and Economic Price on Consumer Preference in bicycle coffee businesses in the Dago area, Bandung City. This study employs a quantitative approach using a survey method. Data were collected through questionnaires measured using a five-point Likert scale and distributed to bicycle coffee consumers. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of validity and reliability testing indicate that all constructs and indicators meet the required measurement criteria. The findings reveal that Mobile Service and Economic Price have a positive and significant effect on Consumer Preference. Simultaneously, both variables explain 59.2% of the variance in consumer preference, with Economic Price identified as the dominant influencing factor. These results indicate that affordable pricing strategies play a critical role in shaping consumer preference, while mobile service supports service accessibility. Keywords: Mobile service; Economic price; Consumer preference; Bicycle coffee; Microenterprise